Evaluation of freshwater prawn, Macrobrachium rosenbergii, for biological solids control in raft aquaponic systems and the protective effectiveness of root guards. Issue 1 (5th November 2021) - Dusci, Joshua C.; Hager, Janelle; Coyle, Shawn; Tidwell, James
Abstract: The accumulation of excess solids within the hydroponic troughs of raft aquaponic systems is considered one of the most common problems in commercial production. These solids can negatively affect water quality during decomposition. They can also impact plant health by physically coating the plant roots, reducing nutrient uptake and inducing plant diseases such as Pythium. Manual removal is labor intensive and costly. Based on their detritivorous feeding behavior, the freshwater prawn, Macrobrachium rosenbergii, may have potential as a biological control of solids. However, in a preliminary trial it was found that prawn will damage unprotected plant roots. To address this, two trials were conducted to evaluate the impact of prawn on solids accumulation within the plant beds and the effectiveness of different mechanical approaches to protect the plant roots. Both trials used six replicate recirculating raft aquaponic systems. Three systems had no prawn and three had prawn (~8 g) stocked at five prawn per trough. The plant grown was Buttercrunch Bibb lettuce ( Lactuca sativa ) at a density of 24 plants/m 2 . Plant growth in Trial 1 was statistically analyzed using a 2 × 3 factorial with the main effects of presence of prawn (none or 5/trough) and root protection device (none, plastic screen, or cloth netting). Water quality and solids data were compared in systems with prawn and without prawn using a two sample t test. Trial 1 lasted 32 days. Trial 2 used a plastic mesh "false bottom" to exclude prawn from access to the plants over the entire beds. Trial 2 used six systems all with the false bottoms in place. The comparison of three systems with prawn and three systems without prawn and was conducted over two plant production cycles of 4 weeks each. All data was analyzed using a two sample t test. In Trial 1, the presence of prawn produced a highly significant ( p  ≤ 0.01) reduction of settled solid wastes within the troughs, but plant growth was significantly reduced ( p  ≤ 0.01) in beds stocked with prawn regardless of root protection device. In Trial 2, the presence of prawn again produced a highly significant ( p  ≤ 0.01) reduction of settled solid waste within the troughs. There was no significant difference ( p  > 0.05) in average plant weight with this root protection device in systems with or without prawn. This research demonstrates that freshwater prawn can reduce solid waste buildup in aquaponic plant beds, but that effective root protection is essential to maintain efficient plant production.